Surface Passivation of Germanium with ALD Al2O3: Impact of Composition and Crystallinity of GeOx Interlayer - Isometsä Joonas; Jahanshah Rad Zahra; Fung Tsun H.; Liu Hanchen; Lehtiö Juha-Pekka; Pasanen Toni P.; Leiviskä Oskari; Miettinen Mikko; Laukkanen Pekka; Kokko Kalevi; Savin Hele; Vähänissi Ville (MDPI, 2025)
Germanium is an excellent material candidate for various applications, such as field effect transistors and radiation detectors/multijunction solar cells, due to its high carrier mobilities and narrow bandgap, respectively. However, the efficient passivation of germanium surfaces remains challenging. Recently, the most promising results have been achieved with atomic-layer-deposited (ALD) Al2O3, but the obtainable surface recombination velocity (SRV) has been very sensitive to the surface state prior to deposition. Based on X-ray photoelectron spectroscopy (XPS) and low-energy electron diffraction (LEED), we show here that the poor SRV obtained with the combination of HF and DIW surface cleaning and ALD Al2O3 results from a Ge suboxide interlayer (GeOx, x < 2) with compromised quality. Nevertheless, our results also demonstrate that both the composition and crystallinity of this oxide layer can be improved with a combination of low-temperature heating and a 300-Langmuir controlled oxidation in an ultrahigh vacuum (LT-UHV treatment). This results in a reduction in the interface defect density (D-it), allowing us to reach SRV values as low as 10 cm/s. Being compatible with most device processes due to the low thermal budget, the LT-UHV treatment could be easily integrated into many future devices and applications.